Structural Integrity Analysis of Nozzleless Booster Propellant Grain in the Process of Curing and Cooling - Kui Bin, Liu Qiang, Na Xudong, Liu Jue (Hangkong bingqi)
In order to accurately evaluate the structural integrity level of the solid rocket ramjet nozzleless booster propellant grain during curing and cooling, the structural integrity of the nozzleless booster propellant grain of a solid rocket ramjet engine under uniform temperature field with linear temperature reduction and non-uniform temperature field considering convective heat transfer between nozzleless booster and environment is calculated by using finite element software, and the results of finite element calculation are compared with the measured results of CT. The results show that the safety coefficient of the grain is 2.88 under uniform temperature field and 2.53 under non-uniform temperature field, and the most dangerous positions are located on the low burning rate grain. The simulation results in non-uniform temperature field are closer to the experiment results. It is necessary to consider the non-uniform temperature field in the integrity analysis of nozzleless booster grain.